2016
DOI: 10.7762/cnr.2016.5.4.261
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Onion Peel Extract on Inflammatory Mediators in Korean Overweight and Obese Women

Abstract: Quercetin, found abundantly in onion peel, has been known to have antioxidant and anti-obesity effects and improves endothelial function. The purpose of this study was to evaluate the effects of a quercetin-rich onion peel extract (OPE) on the inflammatory mediators in overweight and obese women. This study was a randomized double-blind, placebo-controlled study. Thirty-seven healthy overweight and obese women were randomly assigned to two groups, and one group was given a soft capsuled OPE (100 mg quercetin/d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 42 publications
(48 reference statements)
2
22
0
Order By: Relevance
“…In a study by Kim and Yim [70], OPE administration (100 mg/d, 50 mg bis a die) for 12 weeks significantly reduces waist and hip circumference, and the effects are ascribed to the reduced oxidative stress in obese women. However, the follow-up study showed no influence on the inflammatory mediators among the obese women [95].…”
Section: Anti-obesity and Hypolipidemic Effectsmentioning
confidence: 82%
“…In a study by Kim and Yim [70], OPE administration (100 mg/d, 50 mg bis a die) for 12 weeks significantly reduces waist and hip circumference, and the effects are ascribed to the reduced oxidative stress in obese women. However, the follow-up study showed no influence on the inflammatory mediators among the obese women [95].…”
Section: Anti-obesity and Hypolipidemic Effectsmentioning
confidence: 82%
“…When given acutely, quercetin reduced plasma endothelin-1 (Loke et al 2008), reduced blood pressure in overweight volunteers but only of a certain genotype (Egert et al 2010a), but did not reduce urinary F2-isoprostanes (Loke et al 2008), nor blood pressure in normal weight volunteers (Egert et al 2010b). When given in the form of onion skin extract, quercetin did not affect systemic inflammation in overweight women (Kim & Yim 2016), post-prandial blood pressure, endothelial function, serum leptin nor adiponectin in overweight adults (Brull et al 2016(Brull et al , 2017. These various studies suggest that quercetin exerts some effects in humans but the exact effect is highly dependent on the individual's metabolic and genetic status, and on the form given.…”
Section: Human Intervention Studies On the Flavonol Quercetinmentioning
confidence: 90%
“…). When given in the form of onion skin extract, quercetin did not affect systemic inflammation in overweight women (Kim & Yim ), post‐prandial blood pressure, endothelial function, serum leptin nor adiponectin in overweight adults (Brull et al . , ).…”
Section: Human Intervention Studies On the Flavonol Quercetinmentioning
confidence: 99%
“…Previous studies have been mostly carried out on QR (25)(26)(27), an important flavonol in onion. Therefore, we had to compare the results of the present study with QR-based researches.…”
Section: Discussionmentioning
confidence: 99%